Effect of the recombinant chymosins of different origins on the quality and shelf life of soft cheeses - D. S. Myagkonosov; D. V. Abramov; I. N. Delitskaya; G. B. Bukcharina (Пищевые системы)
The effect of the type (bovine chymosin (Chy-max Extra), camel chymosin (Chy-max M), and modified camel chymosin (Chy-max Supreme)) and applied dose (1500, 2500, or 3500 IMCU/100 kg of milk) of milk-clotting enzyme (MCE) on the proteolysis degree, microstructure, rheological and sensory properties of Crescenza soft cheese was studied. The proteolysis degree of cheeses was directly proportional to the general proteolytic activity (PA) and dose of the MCEs added into milk during the cheese production. With an equal dose of the MCEs added into milk, the highest level of proteolysis was noted in the cheese options produced with recombinant bovine chymosin (Chy-max Extra). There were no statistically significant differences (p > 0.05) in the proteolysis degree between the cheese options made with the same doses of the camel chymosin (Chy-max M) and modified chymosin (Chymax Supreme). After 21 days of storage, the cheeses with Chy-max Extra MCE had the most plastic consistency, while the cheeses with Chy-max Supreme MCE had the hardest and most elastic one. Cheeses produced with Chy-max M MCE occupied an intermediate position in terms of consistency density. Recombinant MCEs based on camel chymosin (Chy-max M) and modified chymosin (Chy-max Supreme) with low level of PA, may be recommended for use in the production of soft cheeses. This will extend the shelf life of cheeses by slowing-down the plasticization rate of their consistency.